1996
DOI: 10.7557/2.16.3.1204
|View full text |Cite
|
Sign up to set email alerts
|

Pre-slaughter handling of reindeer bulls {Rangifer tarandus tarandus L.) — effects on technological and sensory meat quality, blood metabolites and muscular and abomasal lesions

Abstract: Forty-one reindeer bulls (age 1 1/2 years) were subjected to different pre-slaughter treatments: herding for a short distance to a grazing corral, selection by use of a lasso, lorry transport and helicopter herding for 1, 2 and 3 days respectively. As control, 9 reindeer were shot without previous handling (in the mountains). The results indicated the traditional selection technique of using a lasso to be the most stressful and glycogen-depleting handling procedure so far studied. In the lasso-selected reindee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 6 publications
3
34
1
3
Order By: Relevance
“…Hoffman (2001a) reported that many game animals tend to produce DFD meat due to prolonged stress during the cropping/harvesting process. Numerous studies on pre-slaughter handling processes of red deer have shown that these animals were also prone to DFD (Wiklund et al, 1995;Malmfors and Wiklund, 1996;Wiklund et al, 1996;Wiklund et al, 2001;Wiklund and Malmfors, 2004). The susceptibility of muscles to DFD differs and is determined mainly by differences in muscle fiber type.…”
Section: Ante-mortem Stressmentioning
confidence: 99%
“…Hoffman (2001a) reported that many game animals tend to produce DFD meat due to prolonged stress during the cropping/harvesting process. Numerous studies on pre-slaughter handling processes of red deer have shown that these animals were also prone to DFD (Wiklund et al, 1995;Malmfors and Wiklund, 1996;Wiklund et al, 1996;Wiklund et al, 2001;Wiklund and Malmfors, 2004). The susceptibility of muscles to DFD differs and is determined mainly by differences in muscle fiber type.…”
Section: Ante-mortem Stressmentioning
confidence: 99%
“…From these studies it was concluded that helicopter herding, lorry transport and lairage at the slaughterhouse did not significantly impair ultimate pH values or glycogen content in the muscles (Wiklund etal., 1995;1996a;1996b). The traditional lasso selection technique however was evidently a very stressful and glycogen-depleting handling procedure (Wiklund et al, 1996b). Furthermore, the sensory quality of the meat appeared to be affected by pre-slaughter handling, as a 'stress-flavour' was detected in meat from reindeer subjected to gathering, lasso selection and helicopter herding, whereas this flavour was not detectable in meat from reindeer shot in the mountains.…”
Section: Introductionmentioning
confidence: 94%
“…The model for comparing muscle and blood parameters and abomasal lesions included the fixed effect of treatment group. When the sensory attributes of the longissimus muscle were compared, the model included the random effect of animal nested within treatment group, as well as the fixed effects of treatment group and panel As in earlier studies (Wiklund et al, 1995;1996a;1996b) pH values were converted in the statistical analyses to hydrogen ion concentrations and when presenting the mean values they were transformed back from estimates on the concentration scale. Standard errors, however, become non-symmettic and error ranges on the pH scale were therefore calculated from the estimated means ± standard errors.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations